A Model of Intracellular Persistence of Pseudomonas aeruginosa in Airway Epithelial Cells. (12th August 2022) - Malet, Julien K.; Hennemann, Lisa C.; Hua, Elizabeth M.-L.; Faure, Emmanuel; Waters, Valerie; Rousseau, Simon; Nguyen, Dao
Abstract : Pseudomonas aeruginosa ( P.a. ) is a major human pathogen capable of causing chronic infections in hosts with weakened barrier functions and host defenses, most notably airway infections commonly observed in individuals with the genetic disorder cystic fibrosis (CF). While mainly described as an extracellular pathogen, previous in vitro studies have described the molecular events leading to P.a. internalization in diverse epithelial cell types. However, the long-term fate of intracellular P.a. remains largely unknown. Here, we developed a model allowing for a better understanding of long-term (up to 120 h) intracellular bacterial survival in the airway epithelial cell line BEAS-2B. Using a tobramycin protection assay, we characterized the internalization, long-term intracellular survival, and cytotoxicity of the lab strain PAO1, as well as clinical CF isolates, and conducted analyses at the single-cell level using confocal microscopy and flow cytometry techniques. We observed that infection at low multiplicity of infection allows for intracellular survival up to 120 h post-infection without causing significant host cytotoxicity. Finally, infection with clinical isolates revealed significant strain-to-strain heterogeneity in intracellular survival, including a high persistence phenotype associated with bacterial replication within host cells. Future studies using this model will further elucidate the host and bacterial mechanisms that promote P. aeruginosa intracellular persistence in airway epithelial cells, a potentially unrecognized bacterial reservoir during chronic infections.